Kajian Aspek Reproduksi dan Estimasi Ekonomi pada Ternak Sapi yang di Inovasi Teknologi Reproduksi - Mas Yedi Sumaryadi; Dadang Mulyadi Saleh; Budi Haryanto; Dedi Herdiansah; Sudrajat Sudrajat; Chotim A Yasin (Agricultural Faculty, 2010)
Study of reproduction and economic estimation aspect in cow which innovated of reproduction technologyABSTRACT.Twenty cows head were used in research to know aspect reproduce and economic estimation in cow which innovated by reproduction technology. All of cows in allocated into two groups at random each 10 heads. The first group come from farmer of co-operation member of Ciamis was used as control without innovated by reproduction technology, that mean the cow was naturally of oestrous and inseminated with frozen semen not a result of separation sex. The second group come from farmer group lumba-lumba innovated with oestrous synchronization which was injected prosolvin of 7.5 mg per headl by intramuscular (i.m.) and super ovulated with injected fertagyl of 150 mg per tail by i.m., and then it oestrous was inseminated with frozen semen result of sex separation. Research result indicates that technically there were difference of performance reproduce in cow which is innovated by reproduction technology than control. It concluded that the improvement of reproduction efficiency in cow after innovated by technology of reproduction in term of type of birth in twin and increasing of male sex up to 12 percent. It is in line with the economic estimation of cow which is technological application of reproduction improves generating revenue up to 22.35 percent per month.